Efeitos do behavior skills training em professores para implementação de tentativas discretas - Batista, Suellen dos Santos (Universidade Federal de São Carlos, 2025)
School inclusion is a complex social process that requires the training of education professionals. The Behavior Skills Training (BST) procedure has been used for skill training and the implementation of Discrete Trial Training (DTT) to promote skill acquisition. Considering that reading skills are fundamental repertoires to be developed in students, and that general education teachers must plan teaching conditions that promote the inclusion of students in special education target groups (PAEE), two studies were conducted. Study 1 aimed to conduct a systematic literature review on the use of BST to train professionals, caregivers, parents, and teachers in the implementation of DTT, seeking to identify the contexts in which this strategy has been applied and whether teacher training for academic skill instruction in school settings has been the focus of research. Searches were conducted in four databases using four keyword combinations, with no publication date restriction. Data were analyzed based on six categories: a) number/type of participants; b) number of participants who completed training; c) design and training procedure; d) DTT components trained; e) characteristics of BST implementation; and f) target behavior. Nine studies were selected for analysis. Most studies focused on training parents of children with developmental delays and professionals, primarily targeting motor imitation and instructional following repertoires. Four studies were related to the school context: one targeted writing and counting behaviors; one worked with special education teachers; and two were conducted in special education schools. The literature review indicated a lack of studies that have integratively investigated the use of BST to train teachers to teach academic skills in school settings. Study 2 aimed to evaluate the effects of BST on training three teachers from 1st and 2nd grade elementary school classrooms to implement three instructional programs—preference assessment, textual behavior, and dictated word-to-written word matching—using DTT. A multiple-probe across participants design was used to assess the effects of BST (independent variable) on teachers’ abilities to implement instructional programs using DTT (dependent variable). Data collection was conducted in eight phases: 1) participant recruitment; 2) participant interviews; 3) initial probe; 4) baseline; 5) BST training (instruction, video modeling, role-play, and feedback); 6) final probe; 7) maintenance probe; and 8) social validity assessment. Results showed that the BST intervention package was effective in teaching relevant skills related to preference assessment, textual behavior, and dictated-to-written word matching. It is concluded that BST is a procedure that can support teacher training, highlighting the importance of investing in research that investigates relevant variables in the continuing education of professionals in the field of education.
Effects of behavior skills training on teachers for the implementation of discrete trials
Keywords: Behavior Skills Training; Ensino por tentativas discretas; Escola regular; Professores; Discrete Trial Training; General Education; Teachers; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade; 3. Saúde e Bem-Estar